On governing and milking cows: replicating good governance practices from East Asia - Bhatta, Gambhir; Gonzalez, Joaquin L.,III (1998)
Governance - in particular, good governance, and how to sustain it - has occupied the agendas of practically all international donors and has caught the attention of policy makers around the world. The United Nations, for one, has woven this concept into its development assistance programme and, in the latest governance programme to be pushed by the UN Development Programme, much emphasis is laid on learning from good governance practices around the world. In this context, the argument here is that, despite the spate of bad publicity received by the countries of this region of late, the UNDP could still pick up a thing or two in the formulation of its governance assistance programme from country experiences in this region. The most important lesson is that institution building is still the key and transparency is vital for the public sector. - Reproduced
Keywords: Public administration - East Asia; Public administration